Строение слуховых центров нижних холмов четверохолмия и внутренних коленчатых тел кролика - Гончаренко, Л.Е.; Квитницкая-Рыжова, Т.Ю.; Степанова, Л.В (Вестник зоологии, 1974)
The cytological composition of the auditory centres of the inferior colliculi of corpora quadrigemina and internal geniculate bodies was studied in healthy rabbits. Three main types of nerve cells are established on the basis of the ratio of cytoplasm and nucleus profiles, character of chromatophilic substance dispersion, and body shape. The auditory centres of the corpora quadrigemina are presented by diffusely arranged nerve cells of the 1st and 3d type; the amount of the 2d type nerve cells is small. The lateral areas of the auditory centres of the internal geniculate bodies involve the 1st type nerve cells, the medial ones -- the 3d type of cells.